(untitled) (Ius Novum, 2021)
The paper addresses the issue of normative character of the provisions of Article 18 § 1–3 of the Penal Code. An attempt has been made - from the standpoint of the determinants of the derivational concept of interpretation of the law and the theory of legislation and rules of legislative technique – to resolve a dispute existing in the science of criminal law concerning whether, in respect of directing the commission of an offence and solicitation of the commission of an offence the provisions of Article 18 § 1 of the Penal Code are provisions supplementing the provision typifying the detailed part of the Penal Code, or whether they express a norm which prohibits directing the commission of an offence or solicitation of the commission of an offence. The first variant of interpretation has been favoured. It was also assumed in the paper that the provisions of Article 18 § 2 and 3 of the Penal Code are not peripheral regulations, but modifiers of the regulations defining the generic type of a prohibited act. Consequently, incitement and aiding and abetting are not separate types of commission of a prohibited act characterised by their own set of statutory traits and they do not supplement the generic description of the type of prohibited act with an additional functional trait. Thus, in any form of criminal complicity, the subjective traits of a generic type of a prohibited act may be identified, including the traits of an executive action.